MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) : BAGAIMANA PENERAPAN DAN KEDALA YANG DIHADAPI OLEH PERGURUAN TINGGI SWASTA DI ACEH - Tuti Marjan Fuadi; Dian Aswita (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The concept Merdeka Belajarhas become an issue that is widely discussed in the world of education, the concept that voices the existence of learning is carried out in preparing the preparation ofuniversity graduates, both public and private, so that they can face the times and changes that are so fast. This article will look at 1) the form of the policy of the Menteri Pendidikan dan Kebudayaan as stated in the 8 Merdeka Belajar Kampus Merdeka programsand their application to privateuniversitiesin Aceh; 2) Obstacles in the implementation of 8 Merdeka Belajar Kampus Merdeka programs at private universities in Aceh.Data was collected through literature studies, news and writings in both online and offline media, as well as interviews with leaders of private universities in Aceh. Furthermore, thedata were analyzed and strengthened with various theoretical supports in the discussion. Through literature study, it was found that there were 8 Merdeka Belajar Kampus Merdeka programs, including; 1) student exchange, 2) internship/work practice, 3) teaching in educational institutions, 4) villageprojects, 5) research, 6) entrepreneurial activities, 7) independent studies and 8) humanitarian projects. Private universities have implemented several programs including studentexchange programs between study programs within universities and student exchanges with study programs outside universities, as well as teaching programs in educational institutions and internships assisted by ministry funds.The challenges faced by private universities in implementing Merdeka Belajar Kampus Merdeka; 1) the adaptation process of the KKNI curriculum with the Merdeka Belajar Kampus Merdeka program, 2) the partner campuses are still limited, 3) thecollaboration of private universities in Aceh with outside parties, both companies, BUMN, BUMD and even the government is still very limited, 4) fund management by foundations that have not budgeted funds for Merdeka Belajar Kampus Merdeka, 5) quality andproductivity of human resources for lecturers and students.